2022
DOI: 10.1186/s12909-022-03920-8
|View full text |Cite
|
Sign up to set email alerts
|

Observed behaviours and suicide assessment language post-Mental Health First Aid training in Australia and the United States: a mixed methods study using discourse analysis

Abstract: Background Mental Health First Aid (MHFA) training teaches participants how to respond to mental health crises, including suicide. Little is known about the impact of training on participants’ observed MHFA behaviours. This exploratory study aimed to compare MHFA-trained Australian and US student pharmacists’ performance and suicide assessment language during simulated patient role-play (SPRP) assessments. Methods Student pharmacists (n = 265) comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…The results of the analysis of official international documents and scientific works showed that the organization of training of pharmacists to provide pharmaceutical care for the mental health of the population is relevant in many countries of the world, i.e. : Australia [4], the USA [5], Great Britain and Ireland [6], Canada [7], New Zealand [8], Granada [8], Sweden [9], Brazil [10] etc.…”
Section: Review and Discussionmentioning
confidence: 99%
“…The results of the analysis of official international documents and scientific works showed that the organization of training of pharmacists to provide pharmaceutical care for the mental health of the population is relevant in many countries of the world, i.e. : Australia [4], the USA [5], Great Britain and Ireland [6], Canada [7], New Zealand [8], Granada [8], Sweden [9], Brazil [10] etc.…”
Section: Review and Discussionmentioning
confidence: 99%